Tadalafil Once Daily Improves Ejaculatory Function, Erectile Function, and Sexual Satisfaction in Men with Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Hyperplasia and Erectile Dysfunction: Results from a Randomized, Placebo‐ and Tamsulosin‐Controlled, 12‐Week Double‐Blind Study. (24th January 2013) - Giuliano, François; Oelke, Matthias; Jungwirth, Andreas; Hatzimouratidis, Konstantinos; Watts, Steven; Cox, David; Viktrup, Lars
Abstract: Introduction: Tadalafil, a long‐acting phosphodiesterase type 5 inhibitor, is approved for treating signs and symptoms of benign prostatic hyperplasia (BPH) and erectile dysfunction (ED); tamsulosin, an alpha‐blocker, is approved for treating signs and symptoms of BPH. Aim: To determine the effects of tadalafil or tamsulosin on sexual function, including ejaculation and orgasm, satisfaction, and erectile function, in sexually active men with ED and lower urinary tract symptoms suggestive of BPH (LUTS/BPH). Methods: A randomized, double‐blind, placebo‐controlled study of tadalafil 5 mg once daily for 12 weeks in men with LUTS/BPH; tamsulosin 0.4 mg once daily was an active control. Main Outcome Measures: The International Index of Erectile Function (IIEF) questionnaire was administered at baseline and 4, 8, and 12 weeks. Analysis of orgasm and ejaculation was post hoc based on the IIEF‐Orgasmic Function (OF) domain (IIEF‐Q9 [ejaculatory frequency] and Q10 [orgasmic frequency]). Other measures included IIEF‐Intercourse Satisfaction (IS), Overall Satisfaction (OS), and Erectile Function (EF) domains. Changes from baseline to 12 weeks (or last observation) vs. placebo were analyzed using analysis of covariance. Higher IIEF scores indicate better functioning. Results: Of 511 study participants, 310 (60.7%) had ED and were sexually active. The IIEF‐OF increased significantly through 12 weeks with tadalafil vs. placebo ( P = 0.048), as did IIEF‐Q9 ( P = 0.045) but not IIEF‐Q10 ( P = 0.100). Compared with placebo, IIEF‐OF, Q9, and Q10 decreased significantly with tamsulosin (all P < 0.05). The IIEF‐IS and OS increased significantly at end point with tadalafil (both P < 0.001); for tamsulosin, change was not significant for IS, while OS decreased significantly ( P = 0.009). The IIEF‐EF domain increased significantly vs. placebo with tadalafil ( P < 0.001) but not tamsulosin ( P = 0.699). Conclusions: Tadalafil 5 mg once daily significantly improved ejaculation and orgasm, intercourse and overall satisfaction, and erectile function. Men receiving tamsulosin 0.4 mg once daily experienced a decrease in both ejaculatory/orgasmic frequency and overall satisfaction vs. placebo, with no significant effect on erectile function.